(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2023)
In this article, activities in the field of culture and industry ideas about the peculiarities of growing creative teams is maintained. Creative teams have a number of features. The most important of them is that the processes taking place within the team are characterized by the struggle of two trends.One Direction is to achieve the team’s Jeeps as a particular social group that requires conformism from its members, while the other is a required creation for an entirely free individual who, by its nature, stands in contrast to conformism.